- Write
f (x) = xy3 + yz3 + zx3 - x3y - y3z - z3x.
First we look for local maxima, so we need to solve
∂f /∂x = ∂f /∂y = ∂f /∂z = 0.
Now
∂f /∂x = y3 +3x2z - z3 -3x2y. If y = z,
then
f (x, y, z) = 0 and this is not a maximum. Thus we may divide by
y - z and then
∂f /∂x = 0 yields
y2 + yz + z2 = 3x2. Similarly
x2 + xz + z2 = 3y2 and
x2 + xy + y2 = 3z2. Adding these three equations, we obtain
(x - y)2 + (y - z)2
+ (z - x)2 = 0, which yields x =
y = z. This does not give a maximum, because
f = 0 in this case,
and we conclude that the maximum of f must occur on the boundary of
the region, so at least one of x, y, z is 0 or 1.
Let's look at f on the side x = 0. Here
f = yz3 - y3z and
0≤y≤1,
0≤z≤1. To find local maxima, we solve
∂f /∂y = ∂f /∂z = 0. This yields
y = z = 0 and f = 0, which is not a maximum, so the maximum occurs on
the edges of the region considered. If y or z = 0, we get f = 0
which is not a maximum. If y = 1, then
f = z3 - z≤ 0, which
won't give a maximum. Finally if z = 1, then f = y - y3. Since
df /dy = 1 - 3y2, we see that f has a maximum at
y = 1/√3.
This gives that the maximum value of f on x = 0 is
1/√3 -1/√33 = 2√3/9.
Similarly if y or z = 0, the maximum value of f is
2√3/9.
Now let's look at f on the side x = 1. Here
f = y3 + yz3 + z - y - y3z - z3. Again we first look for local maxima:
∂f /∂y = 3y2 + z3 -1 - 3y2z. Then
∂f /∂y = 0 yields either z = 1 or
3y2 = z2 + z + 1. If z = 1, then f = 0
which is not a maximum, so
3y2 = z2 + z + 1. Similarly
3z2 = y2 + y + 1.
Adding these two equations, we find that
y2 - y/2 + z2 - z/2 = 1.
Thus
(y - 1/2)2 + (z - 1/2)2 = 3/2. This has no solution in the
region considered
0≤y≤1,
0≤z≤1. Thus f must
have a maximum on one of the edges. If y or z is 0,
then we are back in the previous case. On the other hand if y or
z is 1, then f = 0, which is not a maximum.
We conclude that the maximum value of f on
0≤x≤1,
0≤y≤1,
0≤z≤1 is
2√3/9.
- For each positive integer n, let f (n) denote the number of
sequences of 1's and 3's that sum to n. Then
f (n + 3) = f (n + 2) + f (n), and we have f (1) = 1, f (2) = 1, and f (3) = 2. Thus
f (4) = f (3) + f (1) = 3,
f (5) = f (4) + f (2) = 4,
f (6) = 6, ...,
f (15) = 189,
f (16) = 277. Thus the number of sequences required is 277.
- Let R denote the specified region, i.e.
{(x, y) | x4 + y4≤x2 - x2y2 + y2}. Then R can be described as the region
inside the curve
x4 + x2y2 + y4 = x2 + y2 (
(x, y)≠(0, 0)). This can be rewritten as
(x2 + y2 - xy)(x2 + y2 + xy) = x2 + y2.
Now change to polar coordinates: write
x = r cosθ,
y = r sinθ; then the equation becomes
(r2 - r2cosθsinθ)(r2 + r2cosθsinθ) = r2. Since
r≠ 0
and
2 cosθsinθ = sin 2θ, we now have
r2(1 - (1/4)sin22θ) = 1. Therefore the area A of R is
∬Rr drdθ |
= ∫02π∫0(1-(1/4)sin22θ)-1/2r drdθ = ∫02πdθ/(2(1 - (1/4)sin22θ)) |
|
|
= ∫0π/416 dθ/(3 + cos22θ) = ∫0π/416 sec22θ dθ/(4 + 3 tan22θ). |
|
Now make the substitution
2z = √3tan 2θ, so
dz = √3sec22θ dθ and we obtain
A = (4/√3)∫0∞dz/(1 + z2) = 2π/√3.
- Ceva's theorem applied to the triangle ABC shows that
(AP/PB)(BM/MC)(CN/NA) = 1.
Since BM = MC, we see that
AP/PB = AN/NC and
we deduce that PN is parallel to BC. Therefore
∠NPX = ∠PCB = ∠NAX and we conclude that APXN is a cyclic
quadrilateral. Since that opposite angles of a cyclic quadrilateral
sum to
180o, we see that
∠APX + ∠XNA = 180o, and the result follows.
- Let
T = {an | n∈N} and for t a
positive number, let
At = {n∈N | an≥t}.
Since
∑an = 1 and
an≥ 0 for
all n, we that if
δ > 0, then there are only finitely many
numbers in
T greater than
δ, and also
At is finite. Thus we may label the nonzero elements of
T as
t1, t2, t3,..., where
t1 > t2 > t3 > ... > 0. We shall use the notation
XΔY to indicate the symmetric difference
{X\Y∪Y\X} of two subsets X, Y.
Consider the sum
∑i≥1(ti - ti+1)| AtiΔπ-1Ati|.
Note that
n∈At\π-1At if and only if
an≥t > aπn, and
n∈π-1At\At if and only if
an < t≤aπn. Write an = tp and
aπn = tq.
We have three cases to examine:
-
an = aπn. Then n does not appear in the above sum.
-
an > aπn.
Then p < q and n is in
Atr\π-1Atr
whenever
tp≥tr > tq, that is
q > r≥p
and we get a contribution
(tp - tp+1) + (tp+1 - tp+2) + ... + (tq-1 - tq) = tp - tq = an - aπn = | an - aπn|.
-
an < aπn.
Then p > q and n is in
π-1Atr\Atr
whenever
tq≥tr > tp, that is
p > r≥q
and we get a contribution
(tq - tq+1) + (tq+1 - tq+2) + ... + (tp-1 - tp) = tq - tp = aπn - an = | an - aπn|.
We conclude that
∑n=1∞| an - aπn| = ∑i≥1(ti - ti+1)| AtiΔπAti|,
because
| AtiΔπ-1Ati| = | AtiΔπAti|. Similarly
∑n=1∞| an - aρn| = ∑i≥1(ti - ti+1)| AtiΔρAti|,
and we deduce that
∑n=1∞(| an - aπn| + ∑n=1∞| an - aρn|) = ∑i≥1(ti - ti+1)(| AtiΔπAti| + | AtiΔρAti|).
Therefore
∑i≥1(ti - ti+1)(| AtiΔπAti| + | AtiΔρAti|) < ε. We also have
∑i≥1(ti - ti+1)| Ati| = 1.
Therefore for some i, we must have
| AtiΔπAti| + | AtiΔρAti| < ε| Ati| and the result follows.
- Multiply
a4 -3a2 + 1 by b and subtract
(a3 - 3a)(ab - 1)
to obtain
a3 - 3a + b. Now multiply by b and subtract
a2(ab - 1) to obtain
a2 -3ab + b2. Thus we want
to know when ab - 1 divides (a - b)2 - 1, where a, b are positive
integers. We cannot have a = b, because a2 - 1
does not divide -1. We now assume that a > b.
Suppose ab - 1 does divide
(a - b)2 - 1 where a, b are positive integers. Write
(a - b)2 - 1 = k(ab - 1), where k is an integer. Since
(a - b)2 -1≥ 0, we see that k is nonnegative.
If k = 0, then we have
(a - b)2 = 1, so
a - b = ±1.
In this case, ab - 1 does divide
a4 -3a2 + 1, because
a4 -3a2 +1 = (a2 + a - 1)(a2 - a - 1). We now assume that
k≥1.
Now fix k and choose a, b with b as small as
possible. Then we have
a2 + a(- 2b - kb) + b2 + k - 1 = 0. Consider
the quadratic equation
x2 + x(- 2b - kb) + b2 + k - 1 = 0. This has an
integer root x = a. Let v be its other root. Since the sum of the
roots is 2b + kb, we see that v is also an integer. Also
av = b2 + k - 1. Since
b, k≥1, we see that v is also
positive. We want to show that v < b; if this was not the case,
then we would have
b2 + k - 1≥ab, that is
k≥ab - b2 + 1. We
now obtain
(a - b)2 -1≥(ab - b2 + 1)(ab - 1).
This simplifies to
a2 - ab≥(ab - b2 + 1)ab, that is
a - b≥(ab - b2 + 1)b and we obtain
(a - b)(b2 -1) + b≤ 0, which is not the case.
Thus v < b and we have
v2 + v(- 2b - k) + b2 + k - 1 = 0. Set u = b.
Then we have
(u - v)2 - 1 = k(uv - 1), where u, v are positive and
v < b. By minimality of b, we conclude that
there are no a, b such that
(a - b)2 - 1 = k(ab - 1).
Putting this altogether, the positive integers required are all
a, b such that
b = a±1.
- Note that for fixed x > 1, the sequence 1/fn(x) is decreasing with
respect to n and positive, so the given limit exists which means
that g is well-defined. Next we show that
g(e1/e)≥1/e,
equivalently
limn--> ∞fn(e1/e)≤e. To do this,
we show by induction that
fn(e1/e)≤e for all positive
integers n. Certainly
f1(e1/e) = e1/e≤e. Now if
fn(e1/e)≤e, then
fn+1(e1/e) = (e1/e)fn(e1/e)≤(e1/e)e = e,
so the induction step passes and we have proven that
g(e1/e)≥1/e.
We now prove that g(x) = 0 for all
x > e1/e; this will show
that g is discontinuous at
x = e1/e. We need to prove that
limn--> ∞fn(x) = ∞. If this is not the case, then
we may write
limn--> ∞fn(x) = y where y is a positive
number > 1. We now have
y = limn--> ∞fn(x) = limn--> ∞fn+1(x) = xlimn--> ∞fn(x) = xy.
Therefore
ln y = y ln x and
x = y1/y. Since
(dx/dy)/x = (1 - ln y)/y2, we see by considering the graph of
y1/y that it reaches its maximum when y = e, and we deduce
that
x≤e1/e. This is a contradiction and we conclude that
limn--> ∞fn(x) = 0. Thus we have shown that g(x) is
discontinuous at
x = e1/e.